Asset Gathering by Hedge Fund Firms - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2011)
We explore agency issues within hedge fund firms. We find that firms that launch many funds tend to underperform other firms by between 3 to 5 percent per year after adjusting for risk. These findings are strongest for firms offering funds that pursue many distinct strategies, invest in a variety of geographical regions, locate in a gamut of countries, and offer different base currencies. Our results allow fund investors to distinguish, ex-ante, firms that focus on delivering alpha from those that focus on gathering assets.